Ceramic films and coatings - Wachtman, J. B., 1928-; Haber, Richard A., 1960- (Noyes Publications, 1993)
Overview of areas in ceramic thin films and coatings. Twenty-one widely respected researchers survey the range of applications of ceramic films and coatings and the techniques used to prepare and characterize them. The book is directed toward potential users of the technology and will also provide a broad update for experts in the field. Ceramic films and coatings are active fields of research and widely used areas of technology. The relatively high hardness and inertness of ceramic materials make ceramic coatings of interest for protection of substrate materials against corrosion, oxidation, and wear resistance. The electronic and optical properties of ceramics make these films and coating important to many electronic and optical devices.
Keywords: Ceramic coating.; Thin films.; elektronické knihy; electronic books